Transcranial Doppler sonography follow-up study in mild vascular cognitive impairment - Mariagiovanna Cantone; Manuela Pennisi; Giuseppe Lanza; Raffaele Ferri; Francesco Fisicaro; Francesco Cappellani; Emanuele David; Vito Nicosia; Klizia Cortese; Giovanni Pennisi; Valentina Puglisi; Rita Bella (PLoS ONE, 2025)
Background To date, few data to transcranial Doppler sonography (TCD) are available in patients with mild vascular cognitive impairment (VCI) at risk for vascular or mixed dementia. In a previous study in patients with mild VCI and cerebral small vessels disease, a hemodynamic pattern of cerebral hypoperfusion and enhanced vascular resistance were observed; however, longitudinal data are currently lacking. Here, we perform a clinical, psychopathological, and neurosonological follow-up of patients with VCI in order to monitor any progression and to identify TCD measures to detect it. Methods From the original cohort of 161 patients, 127 with VCI (mean age 73.6 ± 7.1; 67 males) were re-evaluated after 5.0 ± 1.8 years. Namely, the Montreal Cognitive Assessment (MoCA), the 17-items Hamilton Depression Rating Scale (HDRS), and the Stroop Color-Word Interference Test (StroopT) were administered to screen for global cognitive status, to quantify depressive symptoms, and to explore executive functions, respectively. Mean blood flow velocity (MBFV), peak systolic blood flow velocity (PSV), end-diastolic blood flow velocity (EDV), pulsatility index (PI), and resistivity index (RI) were recorded from the middle cerebral artery, bilaterally. Results At follow up, patients exhibited a significant worsening of both MoCA (21.7 ± 2.1 vs. 20.7 ± 2.0) and StroopT scores (57.4 ± 19.4 vs. 59.7 ± 18.6), whereas HDRS showed an improvement, although the mean raw score remained above the cut-off value for depression (10.3 ± 6.6 vs. 9.8 ± 6.3). MBFV, PSV, and EDV showed a significant increase in PSV and PI and a reduction in EDV. When focused to younger patients (<65 years), we confirmed the significant worsening of both MoCA and StroopT but not HDRS, as well as the significant changes in PI and RI. Finally, considering the differences (D) between baseline and follow-up, the following significant correlations emerged, although with a small-to-medium effect size for all of them: positive correlation between MBFV-D and MoCA-D and between RI-D and STROOP-D, and a negative significant correlation between RI-D and MoCA-D. Conclusions Notwithstanding some limitations, such as the lack of a control group and neuroimaging data at follow-up, TCD may contribute to the early detection, monitoring, and management of VCI patients at risk for dementia. Together with compatible clinical and cognitive features, the exploration of early TCD markers that possibly indicate a higher risk of progression might represent an intriguing research direction and a significant clinical perspective.